Climate change threatens unique genetic diversity within the Balkan biodiversity hotspot – The case of the endangered stone crayfish - Leona Lovrenčić; Martina Temunović; Lena Bonassin; Frederic Grandjean; Christopher M. Austin; Ivana Maguire (Global Ecology and Conservation, 2022)
The stone crayfish Austropotamobius torrentium is globally endangered due to anthropogenic pressure on its habitats, climate change and the invasive crayfish species, particularly the signal crayfish Pacifastacus leniusculus. Aiming to guide A. torrentium conservation within the hotspot of its genetic diversity in the western Balkan Peninsula, we combined population genetics and species distribution models (SDMs) to reveal the impact of climate change and the invasive P. leniusculus on A. torrentium diversity. Population genetic analyses based on newly developed microsatellites revealed moderate within-population genetic diversity and high differentiation among populations, reflecting isolated populations with limited gene flow. Alongside strong genetic structuring, we discovered high level of inbreeding coefficient indicating homozygote excess within the majority of populations. The SDMs results predicted substantial reductions of suitable habitats for A. torrentium by 2070; 80 % of its currently suitable habitat is predicted to be lost under high‐warming climate change scenario. Obtained results indicated that 44 % of populations with high and/or unique genetic diversity, including three highly divergent and geographically restricted evolutionary lineages, are located in the areas predicted to become unsuitable in the future, highlighting their vulnerability to extinction. Further, SDMs revealed considerable decrease of future habitat suitability for P. leniusculus, suggesting that climate change represents greater threat to A. torrentium. Our study highlights the importance of conserving remnant A. torrentium populations, among other, through assisted migration and population mixing that could help populations overcome the risks of inbreeding and maladaptation, and thus enabling A. torrentium to withstand the ongoing climate change.